Efektivitas Pembelajaran Berdiferensiasi Model Complex Instruction dan CIRC (Cooperative Integrated Reading And Composition) Terhadap Kemampuan Membaca Pemahaman Untuk Siswa Sekolah Dasar Kelas IV - Laraswati, Anggun; Setyaningtyas, Eunice Widyanti (Jurnal Ilmiah Dikdaya, 2023)
The purpose of this study was to determine differences in the effectiveness of reading comprehension skills based on the differentiated learning methods of complex instruction and CIRC models in fourth grade elementary school students, as well as to determine the higher level of effectiveness between differentiated learning of Complex instruction and CIRC models on reading comprehension abilities in elementary school students. Class IV. This experimental research uses the Non Equivalent Control Group Design design which will use two classes as research subjects, namely the control class and the experimental class. The results showed that when teaching using differentiation was used for fourth grade elementary school students, the CIRC (Cooperative Integrated Reading and Composition) model and the Complex Instruction model provided diverse learning outcomes for students. The experimental class (SD Negeri Suruh 01 Class IV A) got an average score of 97.25 on the post test, compared to the average score of the control class (SD Negeri Suruh 01 Class IV B) which was only 79.35. In the experimental class, students were more involved in group discussions and were better prepared in communicating the results of group work, whereas in the control class, there were still some students who refused to work together in completing assignments given by the teacher. The difference in the application of the learning model to learning outcomes is based on the behavior targeted at students when working in groups. The experimental class, seen from the grades and completeness achieved by each student, has a greater value than the control class.